2020
DOI: 10.3390/su12124974
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Autonomous Road Public Transport Acceptance: A Study of Singapore

Abstract: This study examines the perceptions of concerns and benefits surrounding autonomous road vehicles deployed for public transport, their relationships with public acceptance, and what the public prefers during its implementation. Surveying 210 participants in Singapore, we found a general acceptance of the deployment of autonomous road public transport in Singapore with agreement that introducing them would be beneficial, particularly in improving public transport reliability and accessibility. However, they rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 19 publications
(39 reference statements)
1
13
0
Order By: Relevance
“…On the other hand, research studies where the respondents are either provided a brief description (Chng and Cheah, 2020) or shown a short animated video at the beginning of data collection (Lavieri and Bhat, 2019;Wong and Rinderer, 2020) to familiarize them with the concept of autonomous mobility, were included in the category of 'acceptability' studies. We observed that both acceptability and acceptance of SAMS has been examined and surveyed from several different dimensions including: (1) behavioral intention or willingness to use or adopt the shared services for personal use and/or recommend others to use that when the services are available in the market;…”
Section: Dimensions Of Public Acceptability and Acceptancementioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, research studies where the respondents are either provided a brief description (Chng and Cheah, 2020) or shown a short animated video at the beginning of data collection (Lavieri and Bhat, 2019;Wong and Rinderer, 2020) to familiarize them with the concept of autonomous mobility, were included in the category of 'acceptability' studies. We observed that both acceptability and acceptance of SAMS has been examined and surveyed from several different dimensions including: (1) behavioral intention or willingness to use or adopt the shared services for personal use and/or recommend others to use that when the services are available in the market;…”
Section: Dimensions Of Public Acceptability and Acceptancementioning
confidence: 99%
“…Overall, respondents feel positive about AVs and the services the technology offers. However, studies emphasized that acceptance and subsequent adoption of SAMS depends to a large extent on an individual's trust in the technology and its perceived value (Wong and Rinderer, 2020), benefits, and concerns (Chng and Cheah, 2020).…”
Section: Public Perceptionmentioning
confidence: 99%
See 3 more Smart Citations